Effect of Flow Direction on a Double‐Duty Microreactor for Coproduction of Aniline and Hydrogen. Issue 3 (16th February 2022) - Khazayialiabad, Amirhossein; Iranshahi, Davood
Abstract: A new thermally coupled microreactor, which simultaneously produces hydrogen and aniline, is simulated. It is suggested that the nitrobenzene hydrogenation process, the heat source, occurs in the tube section, thereby providing the requisite energy for the reactor system. Conversely, the shell section contains the steam reforming of glycerol coolant for the exothermic reaction. The results are evaluated in the two flow directions, namely, cocurrent and countercurrent. The furnace and cooling system, vital for the conventional steam reforming and aniline production processes, are eliminated, respectively, having accurately implemented the sensitivity analysis. Optimization of the most effective parameters is performed via genetic algorithm. Abstract : A bifunctional thermally coupled rector comprising glycerol steam reforming and nitrobenzene hydrogenation processes is introduced, enabling simultaneous production of hydrogen and aniline. Furnace and coolant are eliminated. The performance of the reactor in the co‐ and countercurrent flow mode is compared. The process is optimized by a genetic algorithm to improve the reactor performance.